Ngữ pháp - Nguyễn Thị Hồng Anh (Trường Đại học Thuỷ Lợi, 2021)
Bài giảng bao gồm: Articles; Adjectives and adverbs; Conditionals; Linking words and structures; Nouns and Pronouns; Pronouns and Possessives; Relative clause; Reported speech; Statement and Question; Practice; The passive; Words that go together